Made in Japan : (MIT Press, 1997)
In 1989 the MIT Press published Made in America, a landmark study by The MIT Commission on Industrial Productivity, an interdisciplinary group of MIT faculty members. The study analyzed the strengths and weaknesses of American industry and set forth a strategic plan for revitalizing American productivity. Inspired by the MIT study, the Japan Techno-Economics Society formed the Japan Commission on Industrial Performance (JCIP). For three years, seventeen university researchers worked with representatives of thirty-four corporations to analyze the present state of Japanese manufacturing and to identify the challenges Japan will face in the twenty-first century. The result of their study is Made in Japan.